Tendon organ firing during active muscle lengthening in awake, normally behaving cats. - Appenteng, K (1984)
Recordings were obtained of the discharge of single tendon organ (Ib) and muscle spindle (Ia) afferents of the ankle extensor muscles during movement in normal cats. During very slow, smooth increases and decreases in muscle force, Ib afferents showed from one to five stepwise changes in firing rate, attributable to the recruitment of motor units inserting into the receptor capsule. These 'recruitment steps' in Ib firing rate became smoothed and tended to merge during faster variations in muscle force, and were rarely discernible in normal movements such as slow stepping. Rapid imposed stretches resulted in Ib firing patterns which fitted well a dynamic function of whole muscle force. Comparisons were made between the responses of Ib and Ia afferents during rapid, imposed muscle stretch. The segmentation of discharge typical of Ia afferents was not present in Ib afferents, despite segmentation of the e.m.g. of the receptor-bearing muscles. This would imply that Ib afferents exert a rapidly fluctuating reflex action against a relatively steady background of Ib input. Ankle extensor Ib firing during stepping was characterized by feeble firing during the swing phase and substantial, smoothly modulated firing during the stance phase. Taken together with previous chronic recordings, the data support the view that the ensemble of Ib afferents from a muscle signals a dynamic, non-linear function of whole muscle force over a wide range of normal movement.